Estrus Induction and Artificial Insemination in Acyclic Ewes under Field Conditions of Semi-Arid Region of Rajasthan - Saha, S.; Kumar , Davendra; Naqvi, S. M. K. (International Journal of Livestock Research, 2018)
Reproductive efficiency of sheep inhabiting the semi-arid regions of India is relatively low due to inadequate feeding (fodder), lack of concentrate feeding practices and nearly free range management coupled with poor health coverage. Increasing the percentage of lamb crop and number of lambs marketed are the primary two goals of sheep producers. Therefore, this study was undertaken to increase the lambing percentage and produce heavier lambs in farmer’s flock. Regular visits were made in the villages and screened 373 Malpura ewes and out of which 31 were identified as postpartum anestrus / acyclic. All the acyclic ewes were offered proper feeding, mineral supplementation, Vitadae injection and Janova capsule and treated with indigenously developed cost-effective progesterone impregnated intra-vaginal sponges and PMSG for induction of estrus. Estrus was detected by using aproned ram after 24 h of sponge removal till prior to artificial insemination. Out of 17 treated ewes, 15 (88.2%) exhibited estrus within 48 hrs of sponge withdrawal and covered by fixed time artificial insemination with chilled diluted semen of Patanwadi rams. conception rates based on 40, 60 and 90 days non-return and lambing rate were recorded as 33.33% (5/15). Artificial insemination resulted in the birth of five healthy Patanwadi x Malpura crossbred lambs with an average birth weight of 4.00±0.09 kg. The average birth weight of these lambs was significantly (P<0.01) higher than the contemporary Malpura lambs which had an average birth weight of 3.30±0.06 kg in the same flock. The results indicate that estrus induction treatment in anestrus ewes with intra-vaginal sponges and PMSH can effectively be used in sheep under field conditions and A.I. with semen of Patanwadi rams produced heavier lambs from Malpura ewes.